2019
DOI: 10.3390/geosciences9040162
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Variations in the Incidence of Dust Storms in Saudi Arabia Revealed from In Situ Observations

Abstract: Monthly meteorological data from 27 observation stations provided by the Presidency of Meteorology and Environment (PME) of Saudi Arabia were used to analyze the spatial and temporal distribution of atmospheric dust in Saudi Arabia between 2000 and 2016. These data were used to analyze the effects of environmental forcing on the occurrence of dust storms across Saudi Arabia by considering the relationships between dust storm frequency and temperature, precipitation, and wind variables. We reveal a clear season… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 62 publications
1
10
0
Order By: Relevance
“…The synoptic conditions of this dust event are somewhat similar to those of a summer-time dust event reported by Kalenderski and Stenchikov (2016), which was centered over northern Sudan. The dust event we describe here is a typical summer-time dust event caused by high winds driven by strong pressure gradients (Alharbi et al, 2013). Although haboob-type dust events commonly occur in the region, analysis of the RGB pink dust composite (Fig.…”
Section: Case Study Of a Summer-time Dust Eventmentioning
confidence: 95%
“…The synoptic conditions of this dust event are somewhat similar to those of a summer-time dust event reported by Kalenderski and Stenchikov (2016), which was centered over northern Sudan. The dust event we describe here is a typical summer-time dust event caused by high winds driven by strong pressure gradients (Alharbi et al, 2013). Although haboob-type dust events commonly occur in the region, analysis of the RGB pink dust composite (Fig.…”
Section: Case Study Of a Summer-time Dust Eventmentioning
confidence: 95%
“…Due to the topography, drought, light textured topsoil and scant vegetative cover, Saudi Arabia is susceptible to dust and dust storms. Previous studies revealed that the highest incidence of dust storms frequency events occurred during the spring in Saudi Arabia [43][44][45]. The sand-dust events during the spring season carry more coarser than fine particles to Jeddah and the soil originated species contribute mainly to dust storm particles [44].…”
Section: Int J Environ Res Public Health 2019 16 X 3 Of 26mentioning
confidence: 99%
“…The KAUST campus is located in the western Arabian Peninsula, on the east coast of the Red Sea (22.3° N,39.1° E). This area is affected by local dust storms originating from surrounding inland deserts, by non-local dust storms arriving from northeast Africa through the Tokar gap (see, for example, Kalenderski and Stenchikov 2016;Albugami et al, 2019;Kumar et al, 2019), https://doi.org/10.5194/acp-2020-444 Preprint. Discussion started: 8 July 2020 c Author(s) 2020.…”
Section: Study Sitementioning
confidence: 99%